A comparative genomics study of the microbiome and freshwater resistome in Southern Pantanal - de Oliveira, André R.; de Toledo Rós, Bárbara; Jardim, Rodrigo; Kotowski, Nelson; de Barros, Adriana; Pereira, Ricardo H. G.; Almeida, Nalvo Franco; Dávila, Alberto M. R. (Frontiers in Genetics, 2024)
This study explores the resistome and bacterial diversity of two small lakes in the Southern Pantanal, one in Aquidauana sub-region, close to a farm, and one in Abobral sub-region, an environmentally preserved area. Shotgun metagenomic sequencing data from water column samples collected near and far from the floating macrophyte Eichhornia crassipes were used. The Abobral small lake exhibited the highest diversity and abundance of antibiotic resistance genes (ARGs), antibiotic resistance classes (ARGCs), phylum, and genus. RPOB2 and its resistance class, multidrug resistance, were the most abundant ARG and ARGC, respectively. Pseudomonadota was the dominant phylum across all sites, and Streptomyces was the most abundant genus considering all sites.